Studi Optimalisasi Pelayanan Bus Damri Bandara Sultan Hasanuddin - Herawati, Herawati; Mutharuddin, Mutharuddin (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Sultan Hasanuddin Airport is one of the transport nodes that have an important role in ensuringeffective implementation of inter-mode transport and efficient. To realize that goal PT Damri providesairport buses as a service alih nwde to improve accessibilihj to and from the airport. However, theavailabilihJ of the airport is not opti